Maskūt ‘Anhu as a Legal Basis for Ruling on Digital Economic Practices: A Case Study of Online Commerce in East Java - Huda, Nurul; Rohman, Taufiqur; Ningrum, Ifa Khoiria; Ma'arif, M. Jauharul; Ramadhan, Mahendra Utama Cahya (UIN K.H. Abdurrahman Wahid Pekalongan, 2025)
This study examines the role of Maskūt ‘Anhu as a legal basis for determining the compliance of online commerce practices with Sharia law, focusing on online trade cases in three regencies around Bojonegoro, East Java. The research aims to analyze the legitimacy of Maskūt ‘Anhu, its understanding and application among scholars and Islamic legal practitioners, as well as its impact on the dynamics of online commerce in the region. The method used is qualitative research with a case study approach, involving in-depth interviews with 120 online MSME actors and 15 scholars and Islamic legal practitioners. The main findings indicate that Maskūt ‘Anhu is accepted as a flexible and relevant legal foundation for regulating digital trade, with the highest level of understanding in Lamongan (40%) and the lowest in Ngawi (30%). The implications of this study emphasize the importance of Maskūt ‘Anhu in supporting Sharia compliance while encouraging innovation in the Islamic digital economy. This research contributes uniquely by integrating classical ushul fiqh principles into the modern context of online commerce and offers recommendations for developing adaptive Sharia regulations. The findings are relevant for scholars, legal practitioners, and policymakers in strengthening the Sharia-based digital economic ecosystem in Indonesia.